A Novel Approach to The Fabrication of Aluminium Foam Through Pressure Assisted High-Frequency Induction Heated Sinterin2 Dissolution Process (P ASDP) - MUSTAPHA, MAZLI (2010)
It was known that it is difficult' to form a metallurgical bonding in a packed aluminium (AI) powder during solid state sintering due to the encapsulation of AI by a thermo chemically stable Ah03 film which hinders the mass transport mechanism by the diffusion process. The disruption of this oxide film is indeed crucial for achieving strong metallurgical bonding during solid state sintering of AI powder. This is largely due to the ability of this oxide film to serve as a hard shell which prevents the AI particle from establishing a direct contact with adjacent AI particles. This work discusses the improvement made by pressure assisted high-frequency induction heated sintering dissolution process (P ASDP) as opposed to the solid state sintering dissolution process (SSSDP) which was used in producing a much improved open celled AI foam. In the preparation of P ASDP AI foam specimens, the AI powder and the sodium chloride (NaCI) acting as filler material were dry-mixed together in order to prepare homogenously mixture. The blended mixture was then subjected to pressure assisted sintering in which a pressure beyond atmospheric level is externally applied to the specimen during high-frequency induction heated sintering. The embedded filler material was then dissolved in order to leave behind an open-celled AI with the same chemical composition as that of the original AI powder. The final material is highly porous and has an interconnected porosity network. The structure of the resulting material has three levels of porosity (i.e. main cells, windows and microporosity). The cell morphology and the size of AI foam closely matt:h those of the filler materials used. The X-ray diffraction analysis shows that as the content of NaCI is increased to the volume fraction of 60%, no compound of NaCI presents in the foam. The improvement of this P ASDP technique leads to an aluminium foam possessing a high dense of cell wall which can be attained in a much shorter time and possesses superior mechanical properties. The influence of processing parameters on the physical and mechanical of the fabricated foams were studied. The compressibility behaviour of sodium chloride I aluminium (NaCI! AI) specimen with different amount of filler material content was investigated. The Heckel equation was used to assume pressure effect at elevated temperature on the density of the specimen. Due to lower plastic deformation capacity, the specimen with higher content of fillet material exhibited lower compressibility. The relationship was established between the compaction pressure and the density of specimens. Williamson-Hall plot method was also applied to determine the crystallite size and lattice strain of the consolidated samples at various pressures. As can be observed, the crystallite size tends to decrease with increasing NaCI content. Results indicate that the compressive properties (i.e. compressive strength, modulus, and stress at densification) increase with compaction pressure at elevated temperature, sintering temperature and sintering time. Considering all contributing factors in forming AI foam using P ASDP method, statistical evaluation utilising the Taguchi's Design of Experiments were carried out extensively to predict the optimum processing parameters in this work. The processing parameters were analysed based on the Taguchi's signal to noise ratio (SIN) and analysis of variance (ANOV A) which is a major improvement from the conventional Full Factorial Design of Experiment statistical method. Results show that the rnost notable factor influencing the fabrication of AI foam was the compaction at elevated temperature, followed by temperature, time and heating rate of the process. The viability of electrical conductivity as a tool for evaluating variations in morphology of P ASDP AI foam and the influence of processing parameters: volume fraction of leaching agent, compaction pressure at elevated temperature, sintering temperature, sintering time and heating rate on the electrical conductivity of the final foams were investigated. It was found that all the chosen factors have significant effects on the physical and mechanical properties of the foam and AI volume fraction is the most important parameter affecting the relative electrical conductivity and relative density of the resultant foam. The findings also suggests that the relationship between relative electrical conductivity and density of the specimen does not follow the mathematical description given by Skorohod and Solanin, instead the power law seems to be a good characterization of the relationship between experimental data of electrical conductivity and density of the resultant foams. It was observed that the addition of silicon carbide, which was synthesised at lower reaction temperature using structured alteration local silica sand from the carbothermal nitridation process, improved the physical and mechanical properties of the foam.